(untitled) (The Research of Medical Science Review, 2025)
Background: Contagious caprine pleuropneumonia is an infectious respiratory disease of sheep and goat which is caused by Mycoplasma capricolum subspp. capripneumoniae (MCCP). MCCP is a major challenge for livestock production globally. Objective: The aim of the study was Pathological and molecular detection of Mycoplasma capricolum subspp. capripneumoniae in small ruminants of district Dera Ismail Khan, Khyber Pakhtunkhwa Methodology: This study was carried out at molecular pathology laboratory, department of Pathology, University of Veterinary & Animal Sciences Lahore Pakistan from December 2016 to January 2017. A total of 50 blood and tissue samples (25 sheep and 25 goats) were collected from CCPP suspected animals at government slaughter house for molecular assay. Blood and tissue samples were collected for serology, hematology, histopathology and PCR identification. Samples were properly labeled, packed and transported to pathology laboratory, Department of Pathology, University of Veterinary and Animals Sciences (UVAS), Lahore. All the data analysis was done by using SPSS version 20.0 Results: Based on histopathology, animal lungs showed interstitial emphysema with bronchopneumonia. The Epithelial lining of the alveoli and bronchi was extensive interrupted and interlobular area was thickened. Congestion, inflammation and bleeding scattered cells were also observed. A significant association was observed between hematological parameters and cases of MCCP in goat. (p˂0.05). Among all 50 samples only 2 goats samples were considered positive based on PI values ≥ 56 by using C ELISA. Based on PCR only two samples were positive for MCCP in goat. Conclusion: The study concluded that MCCP prevalence is 4% in goat on the basis of cELISA in district Dera Ismail Khan. The cELISA and PCR for MCCP detection in blood is useful diagnostic tool to detect MCCP by using blood sample.